2008
DOI: 10.2343/geochemj.42.273
|View full text |Cite
|
Sign up to set email alerts
|

Sr-Nd isotopic characteristics of eolian deposits in the Erdos Desert and Chinese Loess Plateau: Implications for their provenances

Abstract: Material sources of the northern deserts and the Loess Plateau in China are always one of the critical focuses in Quaternary and paleoclimate fields. In this paper, the method of Sr-Nd isotope geochemistry is applied to explore the relationship in material source between the Erdos desert and Chinese Loess Plateau. The ε Nd (0) value of the <75 µm silicate fraction between -11.8 and -17.2 is more positive in the west than in the east, and its 87 Sr/ 86 Sr ratio varies from 0.719218 to 0.714824 without similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…There are no N830 μm grain-size fractions in any of the samples. The grain-size result of this study agrees with the study of Rao et al (2008), but is greatly different from those of the Chinese loess (Sun, 2004). The N75 μm fractions in alluvial sand samples from mountains near Yinchuan and Baotou comprise 70% and 81%, respectively, and consist of N90% in other alluvial sand samples (Table 1).…”
Section: Grain-size Distribution and Mineralogical Compositionsupporting
confidence: 84%
See 1 more Smart Citation
“…There are no N830 μm grain-size fractions in any of the samples. The grain-size result of this study agrees with the study of Rao et al (2008), but is greatly different from those of the Chinese loess (Sun, 2004). The N75 μm fractions in alluvial sand samples from mountains near Yinchuan and Baotou comprise 70% and 81%, respectively, and consist of N90% in other alluvial sand samples (Table 1).…”
Section: Grain-size Distribution and Mineralogical Compositionsupporting
confidence: 84%
“…In this case, the given components are required to be extracted through mechanical separation and chemical leaching from bulk sediment samples for Sr-Nd isotopic and REE geochemical analyses Chen et al, 2007). In recent years, Sr-Nd isotopic and REE geochemical methods have been widely used to trace the cycle of mineral dust (Liu et al, 1993(Liu et al, , 1994Greaves et al, 1999;Pettke et al, 2000;Svensson et al, 2000;Sun, 2002aSun, ,b, 2005Honda et al, 2004;Nakano et al, 2004Nakano et al, , 2005Yokoo et al, 2004;Chen et al, 2007;Yang et al, 2007b;Rao et al, 2008;Lee et al, 2010). Comparatively, Sr-Nd isotopic and REE geochemical studies of the desert provenance are still few (Chang et al, 2000;Roy and Smykatz-Kloss, 2007;Yang et al, 2007a).…”
Section: Introductionmentioning
confidence: 98%
“…Rao et al [59] found that the ε Nd value of fine grained fraction of Mu Us Desert Based on the age distribution of zircon grains, Xie et al [48] found that the sand in central and south Mongolia comes from the Central Asia Orogen (CAO) and the sand in Ontin Daga Sandy Land is derived from both the CAO and the mountains of North China Craton. This remarkable study demonstrated that sand in the low relief should originate from the surrounding high mountains.…”
Section: Geochemical Differences Between the Psasmentioning
confidence: 99%
“…Eolian dust in the Chinese Loess Plateau is usually considered to originate from the desert areas of northern China, however, which deserts are the source areas of eolian dust deposits in the Loess Plateau is controversial at present (Liu, 1985;Liu et al, 1994;Zhang et al, 1997;Sun, 2002a;Nakano et al, 2004;Yokoo et al, 2004;Chen et al, 2007;Rao et al, 2008a). Northern China is climatically controlled by the upper-level westerly and the low-level East Asian monsoon.…”
Section: Geochemical Evolution Of Eolian Calcite From the Desert Regimentioning
confidence: 98%
“…Primary silicate rocks are responsible for the silicate fraction in the desert sand whereas the carbonate fraction is probably associated with weathering of both marine carbonate and silicate rocks. In recent years, detailed investigations on the bulk samples and silicate fractions of the Chinese deserts have been carried out by using the methods of isotopic and elemental geochemistry to trace the provenance, transport and precipitation of mineral dust (Nakai et al, 1993;Liu et al, 1994;Asahara et al, 1995;Chang et al, 2000;Pettke et al, 2000;Bory et al, 2002;Kanayama et al, 2002a,b;Nakano et al, 2004;Yokoo et al, 2004;Grousset and Biscaye, 2005;Nakano et al, 2005;Rao et al, 2006;Chen et al, 2007;Rao et al, 2008a). However, the knowledge of carbonate geochemistry of the Chinese deserts is still limited (Wang et al, 2005a,b,c).…”
Section: Introductionmentioning
confidence: 96%